2020
DOI: 10.24018/ejfood.2020.2.6.169
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Profile, Mineral Bioavailability, and Sensory Properties of Biscuits Produced from Composite Blends of Wheat, Coconut and Defatted Fluted Pumpkin Seed Flour

Abstract: The objective of this work was to produce biscuits from composite flour of wheat, coconut, and defatted fluted pumpkin seed and to evaluate the mineral bioavailability, amino acid profile and sensory properties of the composite biscuits. Wheat/coconut/defatted fluted pumpkin seed flours were blended in the ratio; 100/0/0, 80/10/10, 70/20/10, 60/30/10, 50/40/10, 40/50/10 and labelled as sample A, B, C, D, E and F respectively. Biscuits were baked with these composite flours using the creaming method. Lysine con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
1
2
2
Order By: Relevance
“…There were indications of increased zinc contents with increase in plantain-velvet beans flour supplementation. The findings of this study are lower than the reports (9.59 -17.92 mg/100 g) obtained for zinc contents of biscuits from composite blends of wheat, coconut and defatted fluted pumpkin seeds flour by Oyet and Chibor (2020). On the flip side, Akujobi (2018) documented (0.64 -0.81 mg/100 g) for zinc contents of cookies from cocoyam and tiger-nut flour blends are lower than the values obtained in this work.…”
Section: Resultscontrasting
confidence: 90%
See 1 more Smart Citation
“…There were indications of increased zinc contents with increase in plantain-velvet beans flour supplementation. The findings of this study are lower than the reports (9.59 -17.92 mg/100 g) obtained for zinc contents of biscuits from composite blends of wheat, coconut and defatted fluted pumpkin seeds flour by Oyet and Chibor (2020). On the flip side, Akujobi (2018) documented (0.64 -0.81 mg/100 g) for zinc contents of cookies from cocoyam and tiger-nut flour blends are lower than the values obtained in this work.…”
Section: Resultscontrasting
confidence: 90%
“…The mean score values for the iron contents of the composite flours ranged from 3.62 to 4.03 mg/100 g with CSD (150 g wheat flour, 105 g plantain flour and 45 g velvet bean flour) significantly (p < 0.05) having the highest value (4.03 mg/100 g) while the least iron content (3.62 mg/g) was observed in CSA (300 g wheat flour). Values of the current study are higher than reports (1.06 -1.36 mg/g) of Onoja et al (2011) for iron contents of bread supplemented with wheat, African yam bean, cowpea, pigeon pea, water yam, cocoyam and plantain flour blends and those reported by Oyet and Chibor (2020) for composite blends of wheat, coconut and defatted fluted pumpkin seeds flour (1.67 -2.82 mg/100 g). Inadequate intakes of micronutrients (Zinc and Iron) have been associated with severe malnutrition, increased disease conditions and mental impairment (Mannay and Shadaksharaswany, 2005).…”
Section: Resultscontrasting
confidence: 82%
“…It also corroborated with 1.54% ash content of instant noodles produced from corn, tapioca and wheat flour blends [32]. Percentage ash content any food showed the amount of minerals contained in that food [34]. The ash results obtained were similar with those recorded by earlier researchers [35].…”
Section: B Proximate Composition Of Noodlessupporting
confidence: 88%
“…Earlier report showed that customers prefer bright yellow noodles that retain a stable colour for 24-48 h after preparation [17]. Texture and colour assessment is essential as it influences product acceptability [18]. Consequently, this work was aimed at evaluating the physicochemical properties, textural and sensory characteristics of noodles produced from wheat and unripe plantain flours composite, spiced with ginger.…”
Section: Introductionmentioning
confidence: 99%
“…The negative effect of dietary fiber on dough formation is minimized by adding an optimal amount of water to the dough formula (16,18). Wheat flour and mixtures of different flour substitutions have varying water absorption capacities (19), so different volumes of water must be added at varying levels of flour substitution (20). Our hypothesis states that the baking time of muffins will vary with water addition level.…”
Section: Introductionmentioning
confidence: 99%